2019
DOI: 10.1155/2019/7631531
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Safety Profile of Four Copaifera Species and of Kaurenoic Acid by Salmonella/Microsome Test

Abstract: Trees of the Copaifera genus are native to the tropical regions of Latin America and Western Africa. Copaifera sp is widely used as a popular medicine and it has various ethnopharmacological indications, including gonorrhea, bronchitis, asthma, skin ulcers, ulcers, sore throat, uterine infections, general inflammations, cancer, and leishmanioses. Kaurenoic acid is a naturally occurring diterpene found in Copaifera and has been used as an anti-inflammatory, treatment of ulcer, leishmaniasis, and cancer. Bearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(75 reference statements)
0
4
0
1
Order By: Relevance
“…Several publications assessing the genotoxicity of kaurenoic acid in vitro and in vivo were retrieved from the literature. In the bacterial reverse mutation assay, kaurenoic acid showed negative results (Damasceno et al., 2019 ; Pezzuto et al., 1985 , 1986 ). In other in vitro studies (micronucleus and comet assay), positive results were reported at high concentrations; however, the level of cytotoxicity was not appropriately estimated (Cavalcanti et al., 2006 ; Cavalcanti et al., 2010 ; Cardoso et al., 2017 ; Pasqualli et al., 2019 ).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications assessing the genotoxicity of kaurenoic acid in vitro and in vivo were retrieved from the literature. In the bacterial reverse mutation assay, kaurenoic acid showed negative results (Damasceno et al., 2019 ; Pezzuto et al., 1985 , 1986 ). In other in vitro studies (micronucleus and comet assay), positive results were reported at high concentrations; however, the level of cytotoxicity was not appropriately estimated (Cavalcanti et al., 2006 ; Cavalcanti et al., 2010 ; Cardoso et al., 2017 ; Pasqualli et al., 2019 ).…”
Section: Assessmentmentioning
confidence: 99%
“…In other in vitro studies (micronucleus and comet assay), positive results were reported at high concentrations; however, the level of cytotoxicity was not appropriately estimated (Cavalcanti et al., 2006 ; Cavalcanti et al., 2010 ; Cardoso et al., 2017 ; Pasqualli et al., 2019 ). When non‐cytotoxic concentrations of kaurenoic acid were tested, negative results were observed (Cano et al., 2017 ; Damasceno et al., 2019 ; Dalenogare et al., 2019 ; Pezzuto et al., 1985 , 1986 ). Only the study by Cano et al., 2017 was performed according to a modified OECD test guideline 487 (2014), while the other studies were not performed according to OECD test guidelines.…”
Section: Assessmentmentioning
confidence: 99%
“…Copaifera is a genus that belongs in the family Fabaceae that was first described by Marcgraf and Piso in 1638. The species that belong to this genus are native to the tropical regions of Latin America (mainly Argentina, Bolivia, and Brazil) and Western Africa (Congo, Cameroon, Guinea and Central African Republic) [ 5 , 6 ]. The Copaifera genus is commonly used in folk medicine in African countries.…”
Section: Introductionmentioning
confidence: 99%
“…New options for the research and development of safe therapies are offered by nanomaterials in conjunction with natural products. Many components present in plants have strong antimicrobial potential and have been used for thousands of years to treat infections, such as fungal infections (Damasceno et al, 2019; Marenaet al, 2020). In addition, alkaloids, phenols, flavonoids, terpenes, quinones, among others, can provide bioavailable and effective drugs (Abad, Ansuategui, & Bermejo, 2007; Mlynarczyk et al, 2021; Resende et al 2012).…”
Section: Introductionmentioning
confidence: 99%